Menentukan Lokasi Gangguan Dengan Metode Simple Reactance Dan Takagi Pada Saluran Distribusi Bangko PT. Chevron Pacific Indonesia Menggunakan Software ETAP 12.6.0 - Yellyna Sari Agus; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Accurate estimastion of fault location is essential for reliability of power system. For this purpose, fault location algorithms are studied and compared in this paper. This paper use two methods for fault location calculation by the short circuit faulted on the distribution line in Bangko PT. Chevron Pacific Indonesia. The two methods used in this paper are simple reactance and takagi. To analyze both methods, various types of short circuit faults were modeled and simulated at various location on a distribution line using ETAP 12.6.0 program. Short circuit types that simulated in this paper are phase to ground (F-G), phase to phase (F-F), phase to pase to ground (F-F-G), and three-phase (F-F-F). Both methods using current and voltage data to calculate the fault distance on the distribution line that obtained from the simulated result data. The percentage error due to simple reactance method and takagi method of single phase to ground and phase to phase faulted were zero. But have a different results for phase to phase to ground (F-F-G) and three phase (F-F-F) faulted by using simple reactance had only one error and takagi obtained by 6 error and had the highest error of 1,2%. The results have shown that the simple reactance method more easier and accurately than takagi method to estimate the location of short circuit faulted on distribution line.Keywords: Fault Location, Short Circuit Faults, Simple Reactance Method, Takagi Method, Software ETAP 12.6.0